Morphological, Histological, and Protein Profiling of Tea Embryo Axis at Early Stage of Culture - Ratna Dewi Eskundari; Taryono Taryono; Didik Indradewa; Yekti Asih Purwestri (Universitas Gadjah Mada, 2021)
Tissue culture is an alternative choice of plant propagation either through somatic embryogenesis or in vitro organogenesis techniques. TRI2025 tea clone has been cultured successfully, however, the scientific information related to morphology, histology, and protein profile at an early event of culturing time has not been reported yet. This study aimed to determine the differences between those pathways, in the context of morphology, histology, and protein profile. The explants were the embryo axis of TRI2025 tea clone cultured on two different induction mediums; somatic embryogenesis and in vitro organogenesis induction medium. The results showed that most of the explants cultured on A medium developed to be a globular-like structure at 11-day after culture (DAC), while all explants cultured on B medium showed the initiation stage of in vitro organogenesis. Histological analysis showed meristem reconstruction at shoot apical meristem (SAM) and root apical meristem (RAM) at 11-DAC at explants cultured on B medium, while explants cultured on A medium showed callusing at 21-DAC. Protein profile analysis using SDS-PAGE showed protein bands of 54 and 81 KDa that only appeared at explants cultured on A medium start from 14-DAC, and those two protein bands thought to be a differentiator at the early stages of the two tissue culture techniques. Thus, these parameters can be used as early detection for plant tissue culture, especially in tea.